SOCIO-ECONOMIC STUDY OF THE SUPPLY OF KISANGANI IN FOOD PRODUCTS AND MANUFACTURING FROM THE ORIGINS TO 2006 - Omer, NGBOLENGE TONGONZE (IJRDO - Journal of Social Science and Humanities Research, 2022)
The Congolese area is larger by 2.345.403 km2 than the African area which extends from 5 0 2’ North latitude to 13 0 15’ South latitude and in longitude East of Greenwich from 12 0 15’ to 31 0 15’. The province of Tshopo alone has an area of 199567 and its population is 2614630. The economy is essentially agricultural export-oriented. The economy was devastated by the multiple wars of rebellions and aggressions of 1964, 1980, 1997 in 2006 several cases of deaths and destruction of the socioeconomic infrastructures of the province as well as by the multiple looting of stores and depots provisions.